Effectiveness of behavioral activation for depression treatment in medical students: Study protocol for a quasi-experimental design - Domínguez Rodríguez, Alejandro; Ramirez Martinez, Flor Rocio; Martínez-Maqueda, Gustavo Iván; Arenas Landgrave, Paulina; Martínez Luna, Sofía Cristina; Salinas Saldivar, Jasshel Teresa (2020)
Depression is a frequent mood disorder among medical students that can lead to multiple negative consequences at individual and social level (such as academic achievement and interpersonal conflicts) as well as patient care performance. Therefore, the need of depression decreasing treatments in medical students is important. This study is designed to evaluate the effectiveness of the Behavioral Activation Treatment for Depression in a sample of Mexican medical students.